THE EFFECT OF CIRCUIT GAMES ON THE PHYSICAL FITNESS OF STUDENTS IN RAPPOCINI STATE PRIMARY SCHOOL MAKASSAR - Juhanis Juhanis; Hasmyati Hasmyati; Benny Benny (Universitas Negeri Medan, 2019)
This research was descriptive research with quantitative approach that aimed to find out; Effects of Games Circuit toward the Physical Fitness Students of Rappocini State Primary School in Makassar. The population was all students of Rappocini State Primary School in Makassar. The samples were all Fifth Grade Students of Rappocini State Primary School in Makassar as many as 30 people. Sampling technique was by purposive sampling technique. Using survey data collection techniques and test measurement. Data analysis technique was descriptive analysis, analysis of t-test by SPSS 21 at significant level α = 0.05. The results of data analysis showed that: the t-test results obtained by value t arithmetic amounted at 26.107 and t table at dk (19) amounted to 2.045 with a significance level of 0.000. There fore the value of t is greater than t table (26.107> 2.045) means no significant effect on the physical fitness of the game circuit on the fifth grade students of Rappocini state primary school in Makassar.